Self Dilation of Esophageal Strictures - Stephen N Sullivan; Marie Corke; William C Watson (Canadian Journal of Gastroenterology)
Over 22 years, 26 patients were taught to dilate their esophageal strictures. Fifteen had peptic strictures, four malignant neoplasms, three achalasia, three dysphagia following fundoplication and one esophageal lichen planus. The patients with peptic strictures (mean age 58 years) did particularly well, repeatedly dilating themselves over an average of six years (range two months to 18 years). There were no serious complications. Self dilation is a safe, convenient and inexpensive way to manage patients who require repeated, frequent dilations for esophageal strictures.